2016
DOI: 10.1007/s10113-016-1033-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends and events through seven centuries: the history of a wetland landscape in the Czech Republic

Abstract: Environmental change can be viewed as the combined result of long-term processes and singular events. While long-term trends appear to be readily available for observation (in the form of temporal comparisons or space-for-time substitution), it is more difficult to gain information on singular events in the past, although these can be equally significant in shaping ecosystems. We examined the past 700 years in the history of a lowland wetland landscape in the Czech Republic with the help of palaeoecological, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The blooms reduce oxygen and block sunlight in the water. As a result, this leads to an excess of nutrients and biodiversity loss, especially the disappearance of many fish species and the growing abundance of some cyprinid fish (Bergström et al 2016, Szabó et al 2017).…”
Section: Climate Change In Helsinkimentioning
confidence: 99%
See 4 more Smart Citations
“…The blooms reduce oxygen and block sunlight in the water. As a result, this leads to an excess of nutrients and biodiversity loss, especially the disappearance of many fish species and the growing abundance of some cyprinid fish (Bergström et al 2016, Szabó et al 2017).…”
Section: Climate Change In Helsinkimentioning
confidence: 99%
“…Moreover, during the course of the years, the Kangaslampi pond has been highly eutrophicated. Indeed, water eutrophication occurs when nutrients in the water increase and threaten the pond's existence (Szabó et al 2017). In 2019, a study was carried out by the city of Helsinki that revealed:…”
Section: Kangaslampi Pondmentioning
confidence: 99%
See 3 more Smart Citations